Oil-in-Water Emulsions Made of Pistachio Oil: Physical and Chemical Properties and Stability - Lama Ismaiel; Valeria Rizzo; Carla Di Mattia; Benedetta Fanesi; Paolo Lucci; Giulia D’Alessio; Deborah Pacetti; Paola Pittia (Foods)
Pistachio nuts are valued for their sensory qualities, nutritional benefits, and health-promoting properties. Pistachio oil has also gained interest for its bioactive compounds, though these are sensitive to processing and environmental stresses. While pistachio-based products are commercially available, little research has addressed the emulsifying properties of crude pistachio oil or its impact on the stability and bioactive profile of oil-in-water (O/W) emulsions. This study evaluated the emulsion-forming abilities of two commercial pistachio oils (PO1, PO2), their physical and oxidative stability during emulsification, and the effects of emulsifier concentration over short-term storage (7 days, 4 °C). O/W emulsions were prepared using 20% (w/w) oil and Tween 20 (0.5% and 1% w/w) in phosphate buffer and homogenized under high pressure. The emulsions were analyzed for particle size, fatty acid profile, antioxidants, and oxidative state. The results revealed differences in fatty acid composition, oxidative stability, and bioactive content between the oils and their emulsions. PO1 showed higher levels of bioactives compared to PO2. Emulsification increased the peroxide value of the oil phase, confirming its pro-oxidant effects. The results of this study demonstrate the potential of pistachio oil to create stable O/W emulsions rich in bioactives, offering new opportunities for healthy emulsified food products.